Emansipasi Wanita Amerika Dari Masa Ke Masa - Aruan, Rumiri (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2011)
This article explains how the American women got theiremancipation from the beginning of 18th century up to mid of 19thcentury. The American women had struggle for their freedom, rights,emancipation, actualization, and discrimination they had from men, evenfrom government. The names such as Betty Friedan, Elizabeth CadyStanton, Elizabeth and Emily Blackwell, were some of the names thatthey had struggle for the American women emancipation. NAWSA, NOW,and ERA, were the result of their fight, and their progress can be seenfrom time to time.Key words: struggle, progress, NAWSA, NOW, and ERA.